(untitled) (Research, Society and Development, 2023)
The restoration of endodontically treated teeth with great loss of tooth structure is a real challenge for dentistry, since it requires the use of materials capable of extending the coronal support and preventing the propagation of fractures. Recently, a change in the use of intraradicular retainers has emerged, creating a new "no post" concept, based on the use of glass fiber reinforced resin composites. The aim of this review is to explore in the literature whether the material, represented by EverX Posterior (GC), presents any advantage of use in comparison with other materials already described for the restoration of endodontically treated teeth. The search was conducted in the main databases, PubMed, Scopus and Web of Science, resulting in 163 articles. After exclusion of duplicates and full-text reading, 14 in vitro articles and 1 clinical article were included in the final analysis version. With regard to the data found, the new biomaterial showed higher fracture resistance in posterior teeth in most of the studies evaluated, except in comparison with indirect restorations, especially the endocrown type. In comparison with direct restorations, EverX Posterior, in a "bilayer", worked as a reinforcement for force distribution and with improved properties in the presence of retentive grooves. For the intraradicular retainers, the new biomaterial also guaranteed an improved mechanical behavior, similar to the comparison made for polyethylene and glass fibers. Thus, further clinical studies should be carried out to confirm the considerations about this philosophy.